Essential spectrum of Schrödinger operators with δ‐interactions on the union of compact Lipschitz hypersurfaces. Issue 1 (29th November 2013) - Behrndt, Jussi; Exner, Pavel; Lotoreichik, Vladimir
Abstract: In this note we prove that the essential spectrum of a Schrödinger operator with δ‐potential supported on a finite number of compact Lipschitz hypersurfaces is given by [0, +∞). We emphasize that the union of a family of Lipschitz hypersurfaces is in general not Lipschitz. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)